STUDI SISTEM PENGGUNAAN UNINTERUPTIBLE POWER SUPPLY (UPS) 400 KVA SEBAGAI CATU DAYA BACK UP PLANT DOVE AND SOAP DI PT UNILEVER OLEOCHEMICAL INDONESIA: STUDY OF SYSTEM USING 400 KVA UNINTERUTIBLE POWER SUPPLY(UPS)AS A DOVE AND SOAP BACK UP PLANT POWER SUPPLY AT PT UNILEVER OLEOCHEMICAL INDONESIA - Silaban, Tabita; Abdullah; Trahman (Politeknik Negeri Medan, 2023)
Abstract Electricity is a basic human need where all human activities always depend on electricity. Pt Unilever Oleochemical Indonesia has two sources as an electrical energy provider, namely Combine Heat and Power (CHP) as the main electrical energy provider and the State Electricity Company (PLN) as a provider of back up electrical energy when CHP experiences a disturbance that causes CHP to shut down. In order not to happen unwanted things, namely the disconnection of the power grid can cause a black out (complete outage). Thus, Uninteruptible Power Supply (UPS) is used as an alternative electrical energy supplier to anticipate sudden power outages while waiting for the activation or synchronization process from CHP to PLN. A UPS is a system that can convert AC voltage into DC and then into AC. the change goes through several stages, In the first stage, the AC voltage supply input is changed to DC by the rectifier (when there is no interferencefrom the source, in the rectifier there is a charge process to charge the battery) and in the next step the inverter converts the DC voltage to AC. Based on the parameter data on the UPS DB 1, the UPS is able to provide power to the load for 1.4 hours (maximum). The UPS load in the soap and dove plant is 63.65% (used 254.6 KVA from 400 kVA), it can still be added to the more load, The greater the battery capacity in a UPS, the UPS will be able to supply power longer than the UPS with a smaller capacity. This report focuses on discussing the length of time a UPS can back up critical loads on soap and dove plants without generators which is done using observation methods in the field. Keywords : System back up, Uninteruptible Power Supplay (UPS), Battery Abstrak Listrik merupakan kebutuhan pokok manusia dimana semua aktifitas manusia selalu bergantung pada listrik. Pada PT Unilever Oleochemical Indonesia memiliki dua sumber sebagai penyedia energi listrik yaitu Combine Heat and Power (CHP) sebagai penyedia energi listrik utama dan Perusahaan Listrik Negara (PLN) sebagai penyedia energi listrik back up saat CHP mengalami gangguan yang menyebabkan CHP harus shut down. Agar tidak terjadi hal yang tidak diinginkan yaitu terputusnya jaringan listrik dapat menyebabkan black out (padam total). Maka, digunakan Uninteruptible Power Supplay (UPS) sebagai pemasok energi listrik alternatif untuk mengantisipasi pemadaman listrik secara tiba tiba sembari menunggu diaktifkannya atau proses sinkronisasi dari CHP ke PLN. UPS adalah suatu sistem yang dapat mengubah tegangan AC menjadi DC lalu menjadi AC. perubahan melewati beberapa tahap, Pada tahap pertama, input suplai tegangan AC diubah manjadi DC oleh rectifier (saat tidak terjadi gangguandari sumber, pada rectifier terjadi proses charge untuk mengisi daya pada baterai) dan pada langkah selanjutnya inverter mengubah tegangan DC menjadi AC. Berdasarkan data parameter pada UPS DB 1, UPS mampu memberikan daya kepada beban selama 1,4 jam (maksimum). Beban UPS di plant soap and dove sebesar 63,65 % (terpakai 254,6 KVA dari 400 kVA), masih dapat dilakukan penambahan beban yang lebih lagi, Semakin besar kapasitas baterai dalam sebuah UPS maka UPS akan mampu mensuplai tenaga lebih lama dari pada UPS dengan kapasitas yang lebih kecil. Laporan ini fokus membahas lama UPS dapat nge back up beban critical pada plant soap and dove tanpa generator yang di lakukan dengan menggunakan metode observasi di lapangan.Kata kunci : Sistem back up, Uninteruptible Power Supplay (UPS), Baterai